Histone deacetylases contribute to excitotoxicity-triggered degeneration of retinal ganglion cells in vivo - Schlüter, Annabelle; Aksan, Bahar; Fioravanti, Rossella; Valente, Sergio; Mai, Antonello; Mauceri, Daniela (Molecular neurobiology, 2019)
Excitotoxicity is known to modulate the nuclear accumulation, and thus activity state, of histone deacetylases (HDACs) in pyramidal neurons. In the retina, deregulation in activity and expression of different HDACs has been linked to pathological conditions such as retinitis pigmentosa, retinal ischemia, glaucoma, and acute optic nerve injury. Up to now, however, the effects of in vivo excitotoxicity on the different HDACs in retinal ganglion cells (RGCs) have not been thoroughly investigated. Here, we injected adult mice intravitreally with N-methyl-D-aspartate (NMDA) as a mean to trigger excitotoxicity-mediated RGC degeneration and we detected time-dependent loss of RGCs at 1 and 7 days after the insult. Further, we characterized the subcellular localization of HDACs belonging to class I (HDAC1, HDAC3), IIa (HDAC4, HDAC5, HDAC7, HDAC9), IIb (HDAC6, HDAC10), and IV (HDAC11) in RGCs. Our analyses revealed a differential pattern of HDACs nuclear distribution in RGCs following excitotoxicity. After 1 day, HDAC3, HDAC5, HDAC6, HDAC7, and HDAC11 showed altered subcellular localization in RGCs while 7 days after the excitotoxic insult, HDAC4 and HDAC9 were the only HDACs displaying changes in their subcellular distribution. Moreover, we found that in vivo selective inhibition of HDAC1/3 or HDAC4/5 via MS-275 (entinostat) or LMK-235, respectively, could prevent ongoing RGC degeneration. In conclusion, our results point towards a role of HDACs in RGC degeneration and identify HDAC1/3 and HDAC4/5 as potential therapeutic targets to treat degenerative retinal diseases.
Gesehen am 08.01.2020